Comparative transcriptomics in B73-teosinte near-isogenic maize lines reveals key defense signaling and phytoalexins in response to Cercospora zeina infection - Sun, Xiaomeng; Zhang, Ruiyu; Wang, Zongping; Zhang, Haotian; Wen, Hairun; Zhang, Junli; Yu, Naibin; Wang, Zhe; Tai, Huanhuan; Yang, Qin (Frontiers in Plant Science, 2025)
Gray leaf spot (GLS), caused by Cercospora zeae-maydis and Cercospora zeina, is a devastating foliar disease affecting maize production worldwide. However, the defense mechanisms underlying GLS resistance are poorly understood. A major quantitative trait locus (QTL), Qgls8, associated with GLS resistance, was previously identified on maize chromosome 8 bin 8.06. Here we conducted transcriptome analyses on leaves from a pair of B73-teosinte near-isogenic lines (NILs) with contrasting Qgls8 alleles infected with C. zeina at 0, 4, 8, and 12 hours post inoculation (hpi). A total of 1225 up-regulated genes (URGs) were identified in the resistant line Qgls8-R compared with the susceptible line Qgls8-S across the four time points. By contrast, 908 URGs were identified in Qgls8-S. The URGs in Qgls8-R were significantly enriched in metabolic processes, phytohormone signaling, and response to biotic stress, while the URGs in Qgls8-S were mostly involved in plant growth and developmental processes. Additionally, C. zeina-induced URGs were consistently enriched in terpenoid metabolism and jasmonic acid (JA) signaling. Terpene- and JA-related genes showed increased expression at least at one time point after C. zeina infection which were confirmed by RT-qPCR. Furthermore, metabolite quantification indicated higher levels of JA and its isoleucine conjugate (JA-Ile) in Qgls8-R compared to Qgls8-S. Weighted gene co-expression network analysis (WGCNA) identified the module “turquoise”, which exhibited the highest positive correlation with Qgls8-R and was related to JA signaling. These findings suggest that the defense response mediated by terpenoid metabolism and the JA signaling pathway plays crucial roles in enhancing GLS resistance following C. zeina infection.